2010
DOI: 10.1007/s00213-010-1925-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural mechanisms underlying acute and repeated administration of antipsychotic drugs in rat avoidance conditioning

Abstract: Rationale Acute antipsychotic treatment disrupts conditioned avoidance responding, and repeated treatment induces a sensitization- or tolerance-like effect. However, the neurochemical mechanisms underlying both acute and repeated antipsychotic effects remain to be determined. Objective The present study examined the neuroreceptor mechanisms of haloperidol, clozapine, and olanzapine effect in a rat two-way conditioned avoidance model. Methods Well-trained Sprague–Dawley rats were administered with haloperid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
114
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 42 publications
(133 citation statements)
references
References 50 publications
19
114
0
Order By: Relevance
“…In the present study as well as our previous ones (Sun et al, 2009;Li et al, 2010), we have observed no differences in behavioral responsiveness to OLZ and CLZ in the induction phase (ie, the repeated drug treatment period), but differences in the expression phase (ie, the challenge test). For example, during the drug treatment period in both the CAR and the PCP-induced hyperlocomotion model (ie, the induction phase), repeated OLZ and CLZ treatment persistently inhibited avoidance response and PCP-induced hyperlocomotion.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In the present study as well as our previous ones (Sun et al, 2009;Li et al, 2010), we have observed no differences in behavioral responsiveness to OLZ and CLZ in the induction phase (ie, the repeated drug treatment period), but differences in the expression phase (ie, the challenge test). For example, during the drug treatment period in both the CAR and the PCP-induced hyperlocomotion model (ie, the induction phase), repeated OLZ and CLZ treatment persistently inhibited avoidance response and PCP-induced hyperlocomotion.…”
Section: Discussionsupporting
confidence: 72%
“…Two doses of OLZ (1.0 and 2.0 mg/ kg) and CLZ (10 and 20 mg/kg) were tested. These doses of OLZ and CLZ produce a reliable and comparable disruption on avoidance responding (Li et al, 2004;Li et al, 2007;Li et al, 2009b;Li et al, 2010;Mead and Li, 2010;Zhang and Li, 2012). On the basis of data from the striatal dopamine D 2 receptor occupancy study in rats (Kapur et al, 2003), we estimated that both drugs at these doses would give rise to a 40-80% striatal D 2 occupancy, which is comparable to values observed in schizophrenic patients (Kapur et al, 1999).…”
Section: Drugs and Choice Of Dosessupporting
confidence: 53%
See 3 more Smart Citations